EFFECTS OF TEACHER–STUDENT RELATIONSHIPS ON PEER HARASSMENT: A MULTILEVEL STUDY. Issue 3 (12th January 2015) - Lucas‐Molina, Beatriz; Williamson, Ariel A.; Pulido, Rosa; Pérez‐Albéniz, Alicia
<x xml:space="preserve">Abstract</x> Peer harassment is a major social problem affecting children and adolescents internationally. Much research has focused on student‐to‐student harassment from either an individual or a multilevel perspective. There is a paucity of multilevel research on students' relationships with the classroom teacher. The purpose of this study was to use a socioecological perspective to examine the relationships between individual student‐level characteristics, problematic teacher–student relationships, and student‐reported peer harassment. A total of 1, 864 children (50.7% female) aged 8 to 13 years (M = 9.82, SD = 1.24), nested in 27 schools (58.2% public) in Spain, participated in the study. Ninety‐four homeroom teachers reported on teacher–student relationships, and students completed self‐report measures related to peer harassment and teacher–student relationships. Multilevel models showed that relationships between students and teachers exerted a varying degree of influence on classroom levels of peer harassment. Specifically, student‐reported teacher support was associated with diminished student‐reported peer victimization, whereas direct and indirect student‐reported teacher‐to‐student aggression was associated with increased peer victimization. Additionally, student‐reported student‐to‐teacher aggression and teacher‐to‐student aggression were associated with increased student‐reported peer aggression. Teacher‐reported variables at the classroom level, however, contributed little to student‐reported outcomes. Results are discussed in the context of future research on relationships between teachers and students.